Influence of Fenofibrate Treatment on Triacylglycerides, Diacylglycerides and Fatty Acids in Fructose Fed Rats - Kopf, Thomas (Public Library of Science, 2014)
Fenofibrate (FF) lowers plasma triglycerides via PPARα activation. Here, we analyzed lipidomic changes upon FF treatment of fructose fed rats. Three groups with 6 animals each were defined as control, fructose-fed and fructose-fed/FF treated. Male Wistar Unilever Rats were subjected to 10% fructose-feeding for 20 days. On day 14, fenofibrate treatment (100 mg/kg p.o.) was initiated and maintained for 7 days. Lipid species in serum were analyzed using mass spectrometry (ESI-MS/MS; LC-FT-MS, GC-MS) on days 0, 14 and 20 in all three groups. In addition, lipid levels in liver and intestine were determined. Short-chain TAGs increased in serum and liver upon fructose-feeding, while almost all TAG-species decreased under FF treatment. Long-chain unsaturated DAG-levels (36:1, 36:2, 36:4, 38:3, 38:4, 38:5) increased upon FF treatment in rat liver and decreased in rat serum. FAs, especially short-chain FAs (12:0, 14:0, 16:0) increased during fructose-challenge. VLDL secretion increased upon fructose-feeding and together with FA-levels decreased to control levels during FF treatment. Fructose challenge of de novo fatty acid synthesis through fatty acid synthase (FAS) may enhance the release of FAs ≤16:0 chain length, a process reversed by FF-mediated PPARα-activation.